2005
DOI: 10.1111/j.1365-2966.2005.09641.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup diffuse light in compact groups of galaxies: HCG 79, 88 and 95

Abstract: Deep B and R images of three Hickson Compact Groups, HCG 79, 88 and 95, have been analysed using a new wavelet technique to measure possible intragroup diffuse light present in these systems. The method used, ov_wav, is a wavelet technique particularly suitable for detecting low surface brightness extended structures, down to a signal‐to‐noise ratio (S/N) = 0.1 per pixel, which corresponds to a 5σ detection level in wavelet space. The three groups studied are in different evolutionary stages, as can be judged … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 72 publications
6
75
0
Order By: Relevance
“…X-ray emission (Ponman et al 1996) and intra-group diffuse light (e.g. Nishiura et al 2000;White et al 2003;Da Rocha & Mendes de Oliveira 2005;Da Rocha et al 2008;Hess et al 2017) have been detected in these objects, confirming their spatial association and intense dynamic activity. We assume a spatial scale of 0.288 kpc arcsec −1 for HCG07, 0.429 kpc arcsec −1 for HCG25 and 0.535 kpc arcsec −1 for HCG98.…”
Section: Datamentioning
confidence: 65%
“…X-ray emission (Ponman et al 1996) and intra-group diffuse light (e.g. Nishiura et al 2000;White et al 2003;Da Rocha & Mendes de Oliveira 2005;Da Rocha et al 2008;Hess et al 2017) have been detected in these objects, confirming their spatial association and intense dynamic activity. We assume a spatial scale of 0.288 kpc arcsec −1 for HCG07, 0.429 kpc arcsec −1 for HCG25 and 0.535 kpc arcsec −1 for HCG98.…”
Section: Datamentioning
confidence: 65%
“…Some works found that ICL colors are consistent with those of the BCG (e.g., Zibetti et al 2005;Krick & Bernstein 2007;Pierini et al 2008;Rudick et al 2010), suggesting that the ICL has been triggered by ongoing interactions among cluster members and the BCG. The merging cluster in the sample of Pierini et al (2008) and some compact groups (Da Rocha & Mendes de Oliveira 2005) represent an exception showing bluer colors for the ICL, hinting at either in-situ star formation or blue dwarf disruption after interaction.…”
Section: Introductionmentioning
confidence: 92%
“…Observational studies show fractions of ICL ranging from a few percent of the total light up to half of it (Feldmeier et al 2004;Da Rocha & Mendes de Oliveira 2005;Zibetti et al 2005;Krick & Bernstein 2007;Gonzalez et al 2007;Da Rocha et al 2008;Guennou et al 2012;Burke et al 2012;Adami et al 2012), depending on enclosing radius and cluster mass. On top of this, there is no common definition of ICL among both observational works and simulations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of pre-processing will depend on the characteristics of the infalling group, such as density and dynamical evolution stage (Da Rocha & Mendes de Oliveira 2005;Da Rocha et al 2005, 2008. Guennou et al (2012) used deep HST ACS data to detect diffuse light for ten clusters between z = 0.4 and 0.8 and did not detect any significant variation in the cluster diffuse light content with redshift.…”
Section: ) Is In Good Agreementmentioning
confidence: 99%